2002
DOI: 10.1073/pnas.112198299
|View full text |Cite
|
Sign up to set email alerts
|

Defective lymphocyte chemotaxis in β-arrestin2- and GRK6-deficient mice

Abstract: Lymphocyte chemotaxis is a complex process by which cells move within tissues and across barriers such as vascular endothelium and is usually stimulated by chemokines such as stromal cell-derived factor-1 (CXCL12) acting via G protein-coupled receptors. Because members of this receptor family are regulated (''desensitized'') by G protein-coupled receptor kinase (GRK)-mediated receptor phosphorylation and ␤-arrestin binding, we examined signaling and chemotactic responses in splenocytes derived from knockout mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
233
2
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 278 publications
(246 citation statements)
references
References 39 publications
(18 reference statements)
10
233
2
1
Order By: Relevance
“…Comparison of the chemotactic responses of T and B cells isolated from GRK5 2/2 or GRK6 2/2 mice indicated that GRK6-deficient cells were impaired in their ability to respond to the chemokine CXCL12 (a selective ligand for the chemokine receptor CXCR4), whereas GRK5-deficient cells were unaffected [43]. The potential role of GRK6 in dopamine receptor regulation has also been highlighted recently in GRK6 2/2 mice, which showed supersensitivity to psychostimulant drugs [44].…”
Section: Grk6mentioning
confidence: 96%
“…Comparison of the chemotactic responses of T and B cells isolated from GRK5 2/2 or GRK6 2/2 mice indicated that GRK6-deficient cells were impaired in their ability to respond to the chemokine CXCL12 (a selective ligand for the chemokine receptor CXCR4), whereas GRK5-deficient cells were unaffected [43]. The potential role of GRK6 in dopamine receptor regulation has also been highlighted recently in GRK6 2/2 mice, which showed supersensitivity to psychostimulant drugs [44].…”
Section: Grk6mentioning
confidence: 96%
“…37 Also, splenocytes derived from β-arrestin 2 knockout mice showed decreased CXCL12-induced migration. 38 Our group recently published a novel role for β-arrestin 1 in cellular migration and metastasis. 39 In colorectal carcinoma cells, prostaglandin E 2 stimulation of the EP4 receptor, a GPCR, leads to increased cellular migration in vitro.…”
Section: β-Arrestin In Cellular Movementmentioning
confidence: 99%
“…For example, β-arrestin-2-dependent stabilization of cytosolic IκBα and inhibition of NF-κB activation following LPS stimulation are essential for rapid and sufficient production of NO in response to microbial attack [14] . Moreover, there is accumulating evidence that β-arrestin-2, which is expressed abundantly in the spleen, is functionally involved in some important immune responses, such as regulation of lymphocyte chemotaxis and homing [24,25] . In the present study we used RNA interference against β-arrestin-2 to test its role in anti-inflammatory effects stimulated by β 2 -AR.…”
Section: Wwwchinapharcom Wang W Et Almentioning
confidence: 99%